2015
DOI: 10.1080/17415977.2015.1017486
|View full text |Cite
|
Sign up to set email alerts
|

Identification of materials in a hyperbolic annular fin for a given temperature requirement

Abstract: This article deals with the prediction of parameters in an annular hyperbolic fin with temperature-dependent thermal conductivity. Three parameters such as thermal conductivity, variable conductivity coefficient and the surface heat transfer coefficient have been predicted for satisfying a prescribed temperature distribution on the surface of fin. This is achieved by a hybrid differential evolution-nonlinear programming optimization method. The effect of random measurement errors is also considered. It is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Based on the given situation, a multitude of possible unknowns may sometimes converge to satisfy a particular objective. 20 Within the purview of porous as well as other type of fins, inverse problems are somewhat fewer in number 20,21 ; albeit, there are several simplified assumptions that deviate from an actual working situation. Complete temperature dependency for all heat transfer modes in porous fins is only available for rectangular geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the given situation, a multitude of possible unknowns may sometimes converge to satisfy a particular objective. 20 Within the purview of porous as well as other type of fins, inverse problems are somewhat fewer in number 20,21 ; albeit, there are several simplified assumptions that deviate from an actual working situation. Complete temperature dependency for all heat transfer modes in porous fins is only available for rectangular geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Una breve revisión de la literatura acerca de los problemas inversos para la estimación de parámetros muestra que en el trabajo de Dasa [7] se predijo la conductividad térmica y el coeficiente de temperatura superficial de una aleta hiperbólica haciendo uso de un algoritmo de optimización. Adicionalmente, Adamsyk [8] describió una técnica experimental combinada con la solución de un problema inverso para la estimación de la conductividad térmica de materiales isótropos y ortótropos haciendo uso de métodos clásicos de optimización tales como Levenberg-Mardquardt.…”
Section: Introductionunclassified
“…6 It has been found that many feasible combinations of unknown parameters involving different materials, sizes, and dissimilar operating conditions can yield the same criterion, which may be a given temperature distribution, power output, or any other performance parameter pertaining to the system behavior. 7,8 As either optimization or regularization is necessary for successfully solving an inverse problem, so, one of the common difficulties encountered in the past is the unavailability of potential algorithms for handling complex problems. Furthermore, earlier optimization methodologies could not perform an intelligent searching to get close to the desired solution.…”
Section: Introductionmentioning
confidence: 99%